Surgical Management of Pulmonary Mycobacterial Disease - Mitchell, John D. (Seminars in Respiratory and Critical Care Medicine, 2018)
There is renewed interest in the use of adjuvant surgical resection in the treatment of pulmonary mycobacterial disease. For pulmonary Mycobacterium tuberculosis, the emergence of significant drug resistance has led clinicians to reconsider surgery in select cases, where a clear benefit in bacterial conversion and cure has been noted. Less data exist for the use of anatomic resection in the setting of pulmonary nontuberculous mycobacterial disease, although multiple reports have supported the use of surgery in select cases. Resection is generally well tolerated, and may often be performed through a minimally invasive approach. While medical treatment clearly remains the mainstay of therapy, more research is needed regarding the use of adjuvant resection in this patient population.
Keywords: drug-resistant tuberculosis; pulmonary nontuberculous mycobacterial disease; thoracic surgery; thoracoscopic surgery; bronchiectasis; cavitary lung disease